Use of Radar to Enhance Shipping Safety on the MV. Tanto Salam: Penggunaan Radar dalam Mendukung Keselamatan Pelayaran di Kapal MV. Tanto Salam - Kurnia, Rahmat; Nurmala, Eka; Hartati, Diah Vitaloka; Dahlan, Harris R.; Balqia, M. Firza (PT. Alpha Trianguli Australis, 2024)
Shipping, or sea transportation, is an essential component of the broader transportation industry, capable of adapting to future changes. It is characterized by its ability to conduct mass transportation effectively. One important tool used in this field is Radar. This navigation device helps ships detect weather conditions and measure distances from certain objects such as debris, boats, and other potential hazards. This research employs a qualitative method to explore the use of Radar on board the MV Tanto Salam. The findings of the study are as follows: 1) Uses of Radar on Board the MV Tanto Salam: Radar serves several functions, including navigation and lane guidance, collision prevention, monitoring weather and sea conditions, detecting buoys and navigation markers, monitoring small and unexpected objects, contributing to automation and integration systems, and assisting with maneuvering and docking at ports; 2) Obstacles in Using Radar on Board the MV Tanto Salam: The study identifies several challenges, including weather disturbances, radio wave interference, blind spots or Radar shadows, limited close-range detection, dependence on manual settings, reduced detection capabilities for small objects, misidentification of objects, technical and maintenance issues, and reliance on operator skills; and 3) Solutions to Overcome Radar Challenges for Enhanced Shipping Safety on MV Tanto Salam: Proposed solutions include enhancing technology through automatic clutter reduction, implementing more sophisticated signal filters, and integrating Radar with other navigation devices. Training for ship crews is also essential to improve their understanding and operation of Radar, particularly in adverse weather conditions or interference-prone areas. Installing additional navigation aids, such as the Automatic Identification System (AIS) and GPS, can also support radar detecting other ships' positions and surrounding objects.